Quercetin Ameliorated Diabetic Stress through Upregulation of Antioxidant Enzymes and the Nrf-2/HO-1 Axis in the Spleen of Mice (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Diabetes is the enduring endocrine complications increasing with tremendous challenges all over the world. Quercetin, being the predominant flavonoids has pentahydroxy polyphenolic structure that bears antioxidant activity. Our study assessed the efficacy of quercetin in mice against diabetes caused oxidative stress by modifying the radical quencher, the body’s antioxidants and their regulator-Nrf-2 and HO-1. Hyperglycemia attributes significantly (p<0.01) raised levels of lipid peroxidation, lowered levels of catalase, GSH, SOD, higher intracellular ROS generation and suppressed Nrf-2/HO-1 reactivity in studied organ (spleen). Quercetin minimizes the sugar level significantly(p<0.01) in blood, causes restoration of altered spleen and body weight, also bring down the lipid peroxide level significantly (p<0.01) and further enhanced SOD, catalase, GSH antioxidant levels. Both splenic & peritoneal macrophages revealed lower intracellular ROS generation. Quercetin uplifted the reactivity of Nrf-2 & HO-1. Study’s outcome showed that quercetin supplementation attenuated diabetes-caused oxidative stress through upregulation of antioxidant enzymes activity and Nrf-2 and its regulated gene-HO-1 in immune organ-spleen. Thus, quercetin might be fruitful in reducing the ROS-mediated damage in diabetic individuals.